2008
DOI: 10.5271/sjweh.1279
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of interventions in preventing injuries in agriculture—a systematic review and meta-analysis

Abstract: Effectiveness of interventions in preventing injuriesObjectives This study reviewed the effectiveness of interventions in preventing occupational injuries among workers in agriculture.Methods Randomized controlled trials, controlled before-after studies, and interrupted time-series studies assessing interventions aimed at preventing injuries among workers in agriculture were considered. MEDLINE and five other databases were searched up to June 2006. Two authors independently assessed the eligibility of studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 14 publications
1
33
0
Order By: Relevance
“…Earlier review studies have pointed out the great shortage of relevant studies regarding interventions to prevent injuries in agriculture (69)(70) and of interventions promoting health and safety for older workers (71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier review studies have pointed out the great shortage of relevant studies regarding interventions to prevent injuries in agriculture (69)(70) and of interventions promoting health and safety for older workers (71)(72)(73).…”
Section: Discussionmentioning
confidence: 99%
“…The findings confirm that participation in education and training is not sufficient to achieve changes in workplace safety practices. Other recent farm-safety programs have called for a comprehensive approach (16,17). The FarmSafe agencies have implemented further educational programs which focus on making an action plan for the farm, and farm skills development courses, which may have a longer-term cumulative impact.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study carried in Scandinavian countries clearly suggested that the most effective intervention to reduce occupational poisonings is represented by banning the highly toxic pesticides (Lehtola et al, 2008). This goal can be achieved by law, at the country level, according to the International Code of Conduct on the Distribution and Use of Pesticides of the Food and Agriculture Organization (FAO) of the United Nations.…”
Section: Occupational Poisonings and Accident Preventionmentioning
confidence: 99%